'Self' (ziji), 'others' (taren) and 'collective' (jiti): Friendships at school embedded with China's Confucian–collectivist sociocultural values. (1st June 2021) - Zhu, Yan
Abstract: Friendship, an important type of interpersonal relationship, has been studied in various disciplines. When studying friendship, sociologists highlight the importance of placing friendships in context to build up a connection between friendship, a type of interpersonal relationship between individuals, and the surrounding social and cultural environment. In sociological studies of friendship, children's friendships in the Chinese context have not been explored thoroughly. To contribute to closing this gap, this article places children's peer friendships in a rural Chinese primary boarding school context and focuses on exploring Chinese Confucian– collectivist sociocultural values that emerged in these children's daily practices of peer friendships.